GEOECOLOGICAL EVALUATION OF SUSTAINABLE DEVELOPMENT OF THE REPUBLIC OF DAGESTAN AND NORMALIZING THE ANTHROPOGENIC BURDEN - Leila Supawna Akhmedov; Raisat Tazutdinovna Radzhabova; N. O. Guseynova; B. M. Kuramagomedov (Юг России: экология, развитие)
Aim. Identifying the laws for natural resources deposits that can and should be the basis for a long-term program of activities for the inevitable and painless transition to renewable fuel energy resources within environmentally acceptable limits.Methods.Methods of measuring and evaluating the sustainability of geosystems are used illustrated in the paper.Results. Basing on a comparative analysis of generalized indexes of population density on the energy supply and food we found patterns that are the theoretical basis for controlling the structure of the economy and settlement in the context of ecological regulation of social and economic policy of the Republic of Dagestan.Conclusions.Latest global evaluation of anthropogenic burden resulting from the geosphere concept allows making significant corrections in previously completed evaluation under the biosphere concept.